2017
DOI: 10.1038/s41598-017-09968-7
|View full text |Cite
|
Sign up to set email alerts
|

Plasma biomarker proteins for detection of human growth hormone administration in athletes

Abstract: Human growth hormone (GH) is a naturally occurring hormone secreted by the pituitary gland with anabolic and growth-promoting activities. Since an increased availability of recombinant GH (rGH) for the treatment of GH-deficient patients, GH has been abused in sports and it is prohibited. “GH-isoform” and “biomarkers” tests are currently available for detection of GH abuse in sports, however both methods suffer from shortcomings. Here, we report on a proteomic approach to search for novel protein biomarkers ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 50 publications
1
22
0
Order By: Relevance
“…The other proteins investigated, VDBP and decorin, did not change in their respective levels during or after the recGH administration, indicating that these proteins are not likely to be informative biomarkers of GH administration in athletes. It needs to be emphasized that in addition to the proteins studied here, some other putative GH biomarkers from omics studies warrant confirmation such as apolipoprotein L1, alpha‐HS‐glycoprotein, lumican, alpha‐1 antitrypsin, total plasma transthyretin, and hemoglobin β subunit 16,26 …”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The other proteins investigated, VDBP and decorin, did not change in their respective levels during or after the recGH administration, indicating that these proteins are not likely to be informative biomarkers of GH administration in athletes. It needs to be emphasized that in addition to the proteins studied here, some other putative GH biomarkers from omics studies warrant confirmation such as apolipoprotein L1, alpha‐HS‐glycoprotein, lumican, alpha‐1 antitrypsin, total plasma transthyretin, and hemoglobin β subunit 16,26 …”
Section: Discussionsupporting
confidence: 88%
“…A large proteomic study was done in relation to 1 month daily administration of 2 mg recGH (2 mg corresponds to 6 IU of recGH). The levels of several proteins were altered, of which alpha‐HS glycoprotein (AHSG) and vitamin D binding protein (VDBP) significantly increased and decreased, respectively 16 . In another proteomics/transcriptomics study, fibronectin 1 (FN1) was identified as a potential biomarker, both the protein and the mRNA levels increased after 3 days of recGH (0.026 mg/kg) treatment 17 .…”
Section: Introductionmentioning
confidence: 99%
“…Similar approach using LC-QTOF was used in the determination of 25 doping-related peptides and 3 metabolites, including GHRPs, GnRHs and anti-diuretic hormones [ 401 ]. Some other LC-MS methods reported focused on the analysis for growth hormone (GH) administration markers such as insulin-like growth factor in human plasma [ 402 ] and its synthetic analogues such as Long R3-IGFI in human plasma [ 403 ]; procollagen III amino-terminal propeptide (P-III-NP) in human serum [ 404 ]; monitoring 22KDa-GH in serum [ 405 ]; four different GHRHs and respective metabolites in human plasma [ 406 ]; 8 proteins biomarker related to recombinant GH administration in samples from athletes [ 407 ]; and 3 recombinant GHs in equine plasma [ 408 ].…”
Section: Challenges – Selected Topic Of Forensic Interestsmentioning
confidence: 99%
“…Currently, proteomics is the most commonly used technique to identify new biomarkers and detect doping violation in human and animal sports. 8,9 Proteomics identifies the set of produced proteins (proteome) in an organism at a defined stage or condition. Different studies have used this technique to detect the use of prohibited substances such as exogenous growth hormone (GH), anabolic steroids, and erythropoiesis-stimulating agents.…”
Section: Using "Omics" In Doping Detectionmentioning
confidence: 99%